2020
DOI: 10.1002/aenm.202002001
|View full text |Cite
|
Sign up to set email alerts
|

Biotriboelectric Nanogenerators: Materials, Structures, and Applications

Abstract: In recent years, triboelectric nanogenerators (TENG) developed by coupling friction electrification and electrostatic induction between two kinds of materials with different triboelectric polarities have attracted much attention for their simple principles, diversified structure, miniaturization, and high energy conversion efficiency. [4] In addition to the large energy sources such as wind, water, and wave, which have been known by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 94 publications
(53 reference statements)
0
57
0
Order By: Relevance
“…[31,32] Chitosan which is obtained from chitin (shells of crabs or shrimp) was observed as a highly electropositive material because of the presence of amino groups in it and used in the fabrication of TENG. [33] Zhong and his peers also explored chitin along with cellulose (from wood and cotton), egg white, silk fiber (from cocoon), and rice paper (from wheat, rice, and corn) for the generation of energy from fully biocompatible TENG. [34] Another research showed the relationship of cellulose content and surface morphology with performance of TENG.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] Chitosan which is obtained from chitin (shells of crabs or shrimp) was observed as a highly electropositive material because of the presence of amino groups in it and used in the fabrication of TENG. [33] Zhong and his peers also explored chitin along with cellulose (from wood and cotton), egg white, silk fiber (from cocoon), and rice paper (from wheat, rice, and corn) for the generation of energy from fully biocompatible TENG. [34] Another research showed the relationship of cellulose content and surface morphology with performance of TENG.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of surface electrification upon contact has been documented for over 2600 years, and many applications have been developed based on this phenomenon. Since 2012, the triboelectric nanogenerator (TENG) proposed by Wang, which uses the coupling of contact electrification and electrostatic induction to generate electrical energy, has been a further understanding of the mechanism of frictional power and gradually developing as one technology in the field of energy harvesting. The operation of a TENG mainly relies on the interfacial electrostatic field, which outputs power due to the displacement current induced by mechanical motion. So far, TENGs can harvest energy from tribo-contacts at the solid-solid interface, solid-liquid interface, liquid-liquid interface, , and even solid-gas interface, while the applications of TENGs have also been successfully developed in many areas, including micro/nano power source, self-powered sensors, blue energy harvester, and high-voltage sources. However, little progress has been proposed related to energy generation at the liquid-gas (L-G) interface. It is commonly known that lightning on rainy days and lightning of dressing coats are the results of triboelectricity, which can be an undeveloped energy source.…”
mentioning
confidence: 99%
“…[30][31][32][33][34] The concept of TENG was first introduced by Wang et al [35] TENGs produce electrical output based on triboelectrification and electrostatic induction in response to external mechanical stimulations. [36][37][38][39][40][41][42] They can be utilized as active sensors via directly correlating the generated electrical signal with the mechanical triggering. TENG-based sensors can use the generated electric signal to self-power themselves as well.…”
Section: Introductionmentioning
confidence: 99%